2006
DOI: 10.1111/j.1365-294x.2006.03031.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Pleistocene refugia of the adder (Vipera berus) as inferred from mitochondrial DNA sequence data

Abstract: In order to contribute to the debate about southern glacial refugia used by temperate species and more northern refugia used by boreal or cold-temperate species, we examined the phylogeography of a widespread snake species (Vipera berus) inhabiting Europe up to the Arctic Circle. The analysis of the mitochondrial DNA (mtDNA) sequence variation in 1043 bp of the cytochrome b gene and in 918 bp of the noncoding control region was performed with phylogenetic approaches. Our results suggest that both the duplicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
159
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(178 citation statements)
references
References 61 publications
(70 reference statements)
14
159
1
4
Order By: Relevance
“…These hybrid zones may be derived from local glacial refugia. Recent studies have suggested that areas of sheltered topography in Central Europe may have provided refugia for woodland species and other temperate plant and animal species (Stewart and Lister 2001;Pinceel et al 2005;Ursenbacher et al 2006). Furthermore it has been clearly indicated that several alpine-subarctic plant species probably survived the glaciations at the periphery of the Alps (Schönswetter et al , 2005Tribsch and Schönswetter 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These hybrid zones may be derived from local glacial refugia. Recent studies have suggested that areas of sheltered topography in Central Europe may have provided refugia for woodland species and other temperate plant and animal species (Stewart and Lister 2001;Pinceel et al 2005;Ursenbacher et al 2006). Furthermore it has been clearly indicated that several alpine-subarctic plant species probably survived the glaciations at the periphery of the Alps (Schönswetter et al , 2005Tribsch and Schönswetter 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the Balkans, a subspecies V. berus bosniensis Boettger, 1889, is known, and in the Far East, V. berus sachalinensis Tsarevski, 1916, has been distinguished. The relationships between these taxa have been studied by Kalyabina-Hauf et al (2004b) and by Ursenbacher et al (2006a).…”
Section: Adders (Vipera Berus Group)mentioning
confidence: 97%
“…Newly founded populations frequently have signals of reduced genetic diversity through founder effects or bottlenecks until they reach equilibrium (e.g., Ibrahim et al 1996). The Carpathian basin, including the Apuseni Mountains, often has been considered a glacial refugium and a genetic center (Botoşaneanu 1975, Deffontaine et al 2005, Sommer and Benecke 2005, Malicky 2006, Ursenbacher et al 2006, Bálint et al 2008. The refugial sources for the southeastern lineage in the more southern Retezat and the Balkans could have been in the Apuseni.…”
Section: ] Population Structure Of Chaetopterygopsis Maclachlanimentioning
confidence: 99%